PROFIL KEMAMPUAN MEMAHAMI MATERI DINAMIKA PARTIKEL PADA SISWA SMA KELAS X - Novitasari, Novitasari (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study aimed to determine profile of understand for Particle Dynamics on senior high school students of Class X. The population in this study was student of Class X from one of senior high schools in Bandung with nine classes in it. Based on the population, sample taken three classes with using purposive sampling technique. Understand was measured is fundamental skill in dimension of cognitive processes in the Revised Bloom’s Taxonomy. Material in this study consist of the kinds of force and Newton Laws. Five cognitive processes was studied in understand. There were interpreting, exemplifying, inferring, comparing, and explaining. The results of study revealed that the percentage of students who interpreting was 56.2%, exemplifying was of 31.5%, inferring was 53.7%, comparing was 48.6%, and explaining was 65.67%. Keywords:Profile, Understand, Particle Dynamics.